2008
DOI: 10.1038/bjp.2008.36
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin promotes nitric oxide function in the ductus arteriosus in the mouse

Abstract: Background and purpose: Prenatal patency of ductus arteriosus is maintained by prostaglandin (PG) E 2 in concert with nitric oxide (NO) and carbon monoxide (CO). Accordingly, we have previously found that NO activity increases upon deletion of either COX. Here, we have examined whether COX inhibition by indomethacin mimics COX deletion in promoting NO. Experimental approach: Experiments were performed in vitro and in vivo with wild-type (WT) and eNOSÀ/À, near-term mouse foetuses. Indomethacin was given p.o. to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
(74 reference statements)
4
32
0
Order By: Relevance
“…Along those lines, Sodinin et al showed that antenatal exposure to indomethacin enhances the • NO activity in the ductus. 9 Another important finding in the present study by Kajimura et al is that use of a NOS inhibitor precursor, L-N G -nitroarginine methyl ester hydrochloride (L-NAME, which undergoes hydrolysis in vivo to produce L-N G -nitroarginine, the functional NOS inhibitor) prevented delayed closure of the ductus after birth in pups from LPS-injected rats. 5 These observations suggest that maternal risk factors, such as chorioamnionitis, can influence the mechanisms of DA regulation, wherein the use of treatments interfering with • NO synthesis or function could be useful adjuncts to achieve PDA closure in this subpopulation of infants, and provide a basis for more targeted interventions on the PDA.…”
supporting
confidence: 55%
“…Along those lines, Sodinin et al showed that antenatal exposure to indomethacin enhances the • NO activity in the ductus. 9 Another important finding in the present study by Kajimura et al is that use of a NOS inhibitor precursor, L-N G -nitroarginine methyl ester hydrochloride (L-NAME, which undergoes hydrolysis in vivo to produce L-N G -nitroarginine, the functional NOS inhibitor) prevented delayed closure of the ductus after birth in pups from LPS-injected rats. 5 These observations suggest that maternal risk factors, such as chorioamnionitis, can influence the mechanisms of DA regulation, wherein the use of treatments interfering with • NO synthesis or function could be useful adjuncts to achieve PDA closure in this subpopulation of infants, and provide a basis for more targeted interventions on the PDA.…”
supporting
confidence: 55%
“…The currently used COX inhibitors carry, in fact, a high incidence of failures due largely, in our view, to the rebound activation of nonPG relaxing mechanisms, NO in particular (26). No such complication is envisaged with an mPGES1 inhibitor.…”
Section: Discussionmentioning
confidence: 96%
“…No firm explanation can be provided with the available data. However, by considering the results in mutants along with work documenting an enhanced NO function upon indomethacin treatment (26), one may conclude that the up-regulatory drive is linked specifically to interference with COX. Extending this reasoning further, one could then assume that COX suppression is coupled with a rebound of parallel pathways in arachidonic acid metabolism (lipoxygenase, monooxygenase) wherefrom a stimulatory signal is generated for the NO system and, particularly for eNOS (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Following NSAID treatment, 30% of infants fail to close their PDA, or after an initially successful closure the PDA will reopen (8,28). This failure to respond to treatment has been attributed to a compensatory increase in vasodilatory nitric oxide production (2,3,29). Recent studies in preterm baboon and human infants demonstrate that treatment of a PDA with a combination of NSAIDs and nitric oxide synthase inhibitors significantly increases the success of ductus closure compared with NSAID treatment alone (16,26).…”
mentioning
confidence: 99%